Statement from the authors of 'Losing sight of women's rights'. Issue 1 (February 2020) - Murray, Kath; Blackburn, Lucy Hunter; Mackenzie, Lisa
Abstract : This statement notes the contribution made by Lisa Mackenzie to the 2019 article 'Losing sight of women's rights: the unregulated introduction of gender self-identification as a case study of policy capture in Scotland' in Scottish Affairs, 28 (3).